Answer:
- x1 = 2.7863
- x2 = - 0.11963
Explanation:
Transform the quadratic to
3x^2 - 8x - 1 = 0
I don't see any obvious factors to this equation so we need to use the quadratic equation.
![\text{x = }\frac{ -b \pm \sqrt{b^(2) - 4ac } }{2a}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iip8v8vwrnlbxa93laserx63mmh528wabp.png)
![\text{x = }( 8 \pm √((-8)^2 - 4*3*(-1) ) )/(2*3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d7g3vz94q7o5v98jmx4mz60jffigczgbuc.png)
![\text{x = }(( 8) \pm √(64 +12 ) )/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g5lkcky1hzeeccz17cjb25vf1swm6okkzf.png)
![\text{x = }(( 8) \pm √(76 ) )/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7w00g86avcku6guq6o97j8t2jhq5646trd.png)
x = (8 +/- 8.7178 ) / 6
x1 = (16.87178)/6 = 2.7863
x2= (8 -8.7178)/6 = -0.1196